The speech of Imam Ali (peace be upon him) at the burial of Fatimah al-Zahra, a consolation for the soul and the eloquence of patience - Mukalf, Prof. PhD Sawadi Farag (Thi Qar Arts Journal, 2022)
Imam Ali addressed his oratory to the messenger of God and gave a salute and peace to him after he had completed Fatima Azzahraa's burial, nearby her father's tomb.In this speech, Imam Ali adopted the style of grievance and soliloquy. His expressions referred to many meanings of sadness and suffering due to the loss of this virtuous wife.This state reminded him of how he lost the messenger of God and how he did the mission of his bod-washing and burying him, stating that patience and reward will be taken into consideration by Alla owing to this painful loss. The influence of Quran was very clear in this abridged speech which expresses many meanings and indications with reference to the tyranny and aggression launched against the daughter of the messenger of Alla wich was considered the cause of her speedy following with her father and her departure from the world.